THE EFFECTIVENESS OF THE GROUP INVESTIGATION (GI) AND THINK PAIR SHARE (TPS) COOPERATIVE LEARNING MODELS ON THE LEARNING RESULTS OF JUNIOR HIGH SCHOOL VIII STUDENTS - Reza Yuliansyah; Uus Kusdinar (Universitas Ahmad Dahlan, 2019)
This research was initiated against the backdrop from a lack of enthusiasm about her three-way students in participating in learning to promote disorder to mathematics; the learning process is still had been centered on teachers are and lack of variation the use of kind of classroom in the learning process. The research aims to understand the whereabouts of the difference of the results learn math and effectiveness study results that use learning model cooperative type Group Investigation ( GI ) and Think Pair Share ( TPS ) to their students class VIII State Junior High School (SMP Negeri) 2 Pajangan Bantul. The research population is a student VIII at SMP 2 Pajangan Bantul in the academic year 2017/2018, Consisting of 4 classes. The sample took two classes, class VIII C as a class experiment 1 and class VIII B as a class experiment 2, was randomly selected, and agreed with the tutor. This research is research his experiments using to form designs experiment design research used is post-test-only control design. Technique analysis the data used to test a prerequisite is test normality, a test of homogeneity, and the hypothesis covering test-t. Based on the results of test-t two parties obtained t_count= 2.25126 and t_table= 2.00134 so t_count>t_table means that there are significant differences between the results of learning math on the kids who taught by using learning model cooperative type GI than students who had by using learning model TPS on class VIII SMP 2 Pajangan Bantul. Moreover, based on the results of the t-test, one hand obtained t_count= 2.25126 and t_table= 2.00134, so t_count>t_table, which means that learning model cooperative type GI more important than the learning model think twisted share on class VIII SMP 2 Pajangan Bantul.